2018
DOI: 10.14257/ijca.2018.11.9.01
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for the Distorted WDM Signals through Dispersion-managed Optical Links Combined with Non-midway Optical Phase Conjugation

Abstract: Dispersion-managed optical link with optical phase conjugator (OPC) at the midway is well known for the compensation technique of optical signal distortion due to group velocity dispersion and fiber nonlinearities. However, in this link, the midway position of OPC restricts the flexible optical link configuration. That is, the OPC position has to get out of the midway for implementation of the flexible link configuration. Therefore, the proponents of this study demonstrated the compensation effect of the non-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Through previous studies, the authors also confirmed that the dispersion map optimization has significant effect on signal distortion compensation in SMF-based WDM systems [12,13]. Furthermore, even in the system where the OPC is not located in the middle of the entire transmission line (i.e., non-midway OPC system), we have confirmed that the improved compensation for the entire WDM signal can be obtained by applying a properly designed dispersion map considering the WDM channel data-rate, modulation format, and OPC location [13].…”
Section: Introductionmentioning
confidence: 57%
“…Through previous studies, the authors also confirmed that the dispersion map optimization has significant effect on signal distortion compensation in SMF-based WDM systems [12,13]. Furthermore, even in the system where the OPC is not located in the middle of the entire transmission line (i.e., non-midway OPC system), we have confirmed that the improved compensation for the entire WDM signal can be obtained by applying a properly designed dispersion map considering the WDM channel data-rate, modulation format, and OPC location [13].…”
Section: Introductionmentioning
confidence: 57%
“…Additionally, the SPM-induced power margin depends on the dispersion map, as well as the DCF's position with respect to the SMF [11,19]. Authors also have shown the dependence of compensation degree on the deployment of the SMF and DCF in a dispersion-managed optical link combined with the OPC [20,21]. In this work, to compensate for the WDM signal distortion caused by the combined effect of GVD and SPM, the various and special dispersion maps are proposed in the dispersion-managed optical link combined with MSSI.…”
Section: Introductionmentioning
confidence: 98%